Re-establishment rate of reindeer lichen species following conventional disc trenching and HuMinMix soil preparation in Pinus -lichen clear-cut stands: a survey study in northern Sweden - Roturier, Samuel; Sundén, Maria; Bergsten, Urban (Scandinavian Journal of Forest Research, 2011)
International audience